2016
DOI: 10.3390/su8030246
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Environmental Performance Evaluation of Thailand’s Food Industry Using Structural Equation Modeling and Fuzzy Analytic Hierarchy Techniques

Abstract: Currently, the environment and sustainability are important topics for every industry. The food industry is particularly complicated in this regard because of the dynamic and complex character of food products and their production. This study uses structural equation modeling (SEM) and a fuzzy analytic hierarchy process (FAHP) to investigate which factors are suitable for evaluating the environmental performance of Thailand's food industry. A first-stage questionnaire survey was conducted with 178 managers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…EM practices to support environment sustainability include, among others, TQM as stated by Garrod and Chadwick [59], Theyel [60] and Yang et al [52]. Besides this, Pipatprapa et al [61] more recently showed that quality management has a significantly positive effect on environmental performance. Therefore, in order to become effective, the EM system should be part of an IMS and must belong to a wider strategy, which should include TQM [62,63].…”
Section: Csfs Common To Em and Tqmmentioning
confidence: 99%
“…EM practices to support environment sustainability include, among others, TQM as stated by Garrod and Chadwick [59], Theyel [60] and Yang et al [52]. Besides this, Pipatprapa et al [61] more recently showed that quality management has a significantly positive effect on environmental performance. Therefore, in order to become effective, the EM system should be part of an IMS and must belong to a wider strategy, which should include TQM [62,63].…”
Section: Csfs Common To Em and Tqmmentioning
confidence: 99%
“…Pipatprapa et al [31] applied the hybrid structural equation modeling (SEM) and the fuzzy analytic hierarchy process (FAHP) approach to find out factors that are influential on the environmental performance of Thailand's food industry. The results showed that quality management, market orientation, and innovation capability have significantly positive effects on the environmental performance.…”
Section: Competitive and Sustainable Manufacturing Approachesmentioning
confidence: 99%
“…Other standards are also considered to be important for the sector, such as the BRC and IFS food safety standards. Until recently, the sector was totally focused on quality, but recently there has been a shift towards environmental aspects, which may suggest that the ISO 9001 quality standard has been a facilitating element in this process, coinciding with studies carried out in various other countries [25,29,50,103].…”
Section: Discussionmentioning
confidence: 99%